2007
DOI: 10.1103/physrevlett.99.258101
|View full text |Cite
|
Sign up to set email alerts
|

Theory of Swimming Filaments in Viscoelastic Media

Abstract: Motivated by the swimming of sperm in the non-Newtonian fluids of the female mammalian reproductive tract, we examine the swimming of filaments in the nonlinear viscoelastic Upper Convected Maxwell model. We obtain the swimming velocity and hydrodynamic force exerted on an infinitely long cylinder with prescribed beating pattern. We use these results to examine the swimming of a simplified sliding-filament model for a sperm flagellum. Viscoelasticity tends to decrease swimming speed, and changes in the beating… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
166
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 161 publications
(175 citation statements)
references
References 20 publications
8
166
1
Order By: Relevance
“…The importance of elastic effects are quantified by the Deborah number De, defined as the ratio of the relaxation time τ of the fluid to the characteristic time scale of the swimmer. For an infinite sheet or filament deformed by low-amplitude traveling waves and suspended in a dilute polymer solution described by the Oldroyd-B model, the swimming speed is always less than the Newtonian speed and decreases with increasing Deborah number (7)(8)(9). These theoretical predictions agree roughly with the measurements of swimming C. elegans (6).…”
supporting
confidence: 80%
See 1 more Smart Citation
“…The importance of elastic effects are quantified by the Deborah number De, defined as the ratio of the relaxation time τ of the fluid to the characteristic time scale of the swimmer. For an infinite sheet or filament deformed by low-amplitude traveling waves and suspended in a dilute polymer solution described by the Oldroyd-B model, the swimming speed is always less than the Newtonian speed and decreases with increasing Deborah number (7)(8)(9). These theoretical predictions agree roughly with the measurements of swimming C. elegans (6).…”
supporting
confidence: 80%
“…There are several natural directions for further study. The discrepancy between the experiment and the predictions for the swimming speed of a filament supporting small-amplitude helical traveling waves (8) suggests that unlike the Newtonian case, rigidly rotating helices and filaments with propagating helical waves behave differently in a viscoelastic medium. Because the discrepancy emerges at small Deborah number, it would be useful to make an expansion about the Newtonian case for small De, as has been done for spheres falling near a wall in a weakly viscoelastic fluid (28).…”
Section: Discussionmentioning
confidence: 40%
“…From the parameterized shape, we computed the center of mass and the average orientation of the bacteria and then calculated swimming speed along the direction of the mean orientation. We found that translocating bacteria in the 3-5% gelatin matrices swam without slipping (i.e., the swimming speed was equal to the wave speed), as has been observed for Leptonema illini in 1% methylcellulose solution (29) but is not predicted by any current theories for swimming in nonNewtonian fluids (9,12,13,30). In the 2% matrices, translocating bacteria sometimes slip with respect to the matrix but still typically swim without slipping.…”
Section: Gelatin Concentration Affects Binding Of Spirochetes To the mentioning
confidence: 64%
“…Changes in the wave shape and frequency of the beating flagellum may enhance the ability of mammalian sperm to move through viscoelastic fluids, such as cervical mucus (8). Recent theoretical work has tried to explain how viscoelastic or gel-like media affect the swimming of microorganisms (9)(10)(11)(12)(13)(14), but, to date, there have been very few empirical studies to test the theoretical predictions (7).…”
mentioning
confidence: 99%
“…One exception is the literature on swimmers wherein models have been developed for a single organism or a few organisms that propel themselves in viscous [48][49][50][51][52][53][54][55][56][57][58] and non-Newtonian fluids [57,[59][60][61][62][63][64][65][66][67]. In particular, swarming hydrodynamic theories have been derived wherein swimmer densities with or without fluid flows are described as continuous fields [4,19,68,69].…”
mentioning
confidence: 99%